“Reparar algo de esta maldita historia”: Memorias del pasado negro y narrativa estatal en Argentina - Monkevicius, Paola Carolina (2015)
This article examines the ways in which the Argentinian state has reintroduced accounts of black history within a national narrative aimed at incorporating and visibilizating cultural minorities. Specifically, we analyze how new meanings and uses of the “Afro” past are constructed by hegemonic sectors, focusing on the commemoration event held at the National Congress to celebrate Afro-Argentineans’ and Afro-Culture Day for the first time. It seems that this commemoration is an opportunity to analyze new forms of visibilization of the black presence in Argentina since it offers a privileged instance for the installation, circulation and transmission of meanings and practices regarding the past on the part of the various actors involved. Finally, the ethnographic work based on participant observation conducted within the context of the above-mentioned ceremonies allows us to conclude that subordinate forms of memory are updated from hegemonic spaces, empowering alternative versions that are introduced in the public scene and find support even within (and in part of) the state acting as an active interlocutor.